Optimization of the phytotoxic effect of herbicide mixtures in winter wheat crops of agrocenoses of the steppe ecotype - Shevchenko, M. S.; Шевченко, М.С.; Mytsyk, Oleksandr; Мицик, Олександр Олександрович; Shevchenko, Sergey; Шевченко, Сергій Михайлович; Poznyak, Vasiliy; Позняк, Василь Васильович; Tkalich, Yuriy; Ткаліч, Юрій Ігоревич (Дніпровський державний аграрно-економічний університет, 2022)
Abstract. Grain productivity of winter wheat largely depends on the degree of weeds, the effectiveness of herbicide application, and soil and climatic conditions. We conducted field tests of new formulations of herbicides on winter wheat crops, aimed at optimizing the phytotoxic composition of tank mixtures consisting of multi-spectrum active substances. When performing the study, we used the general scientific and special research methods for studying the species composition of weeds, evaluating the technical effectiveness of herbicides, biometric indicators of plants and accounting for grain yield. Species identification of weed phytocenosis in winter wheat crops showed weed invasion by ragweed and sunflower. We studied the phytotoxic properties of tank mixtures of herbicides based on the active substance thifensulfuron-methyl, tribenuron-methyl, florasulam and combined preparations based on halauxifen-methyl, florasulam, cloquintocet acid and florasulam, aminopyralid, 2-ethylhexyl ether 2,4-D, their technical efficiency, dynamics of weed inhibition and death during the crop growing season, and individual resistance of the weed species. We carried out a biometric analysis (seeding density, linear growth, yield of grain from the ear) of winter wheat depending on the toxicity of herbicides. We concluded that the mixture of herbicides Granstar Gold 30 g/ha + Hammer 20 g/ha was the most effective. The relevance of the problems we considered in the article is enhanced by the broad potential of improving the weed control system in highly variable phytocenoses in crop rotations of modern adaptive agriculture and ensuring environmental safety. Анотація. Зернова продуктивність озимої пшениці значною мірою залежить від забур’яненості, ефективності застосування гербіцидів, ґрунтово-кліматичних умов. Проведено польові випробування нових рецептур гербіцидів на посівах озимої пшениці, спрямованих на оптимізацію фітотоксичного складу бакових сумішей, що складаються з різноспектральних діючих речовин. При проведенні досліджень використовували загальнонаукові та спеціальні методи дослідження вивчення видового складу бур’янів, оцінки технічної ефективності гербіцидів, біометричних показників рослин та обліку врожаю зерна. Видова ідентифікація фітоценозу бур’янів у посівах озимої пшениці показала забур’яненість амброзії полинолистої та соняшнику. Вивчали фітотоксичні властивості бакових сумішей гербіцидів на основі діючих речовин тифенсульфурон-метил, трибенурон-метил, флорасулам та комбінованих препаратів на основі галауксифен-метилу, флорасуламу, кловінтоцетової кислоти та флорасуламу, амінопіраліду, 2-етилгексилового ефіру 2,4- Д, їх технічну ефективність, динаміку пригнічення та загибелі бур’янів протягом вегетації культури та індивідуальну стійкість видів бур’янів. Проведено біометричний аналіз (густота посіву, лінійний ріст, вихід зерна з колосу) пшениці озимої залежно від токсичності гербіцидів. Дійшли висновку, що найбільш ефективною виявилася суміш гербіцидів Гранстар Голд 30 г/га + Молот 20 г/га. Актуальність проблем, які ми розглядали у статті, посилюється широким потенціалом удосконалення системи боротьби з бур’янами у високоваріабельних фітоценозах у сівозмінах сучасного адаптивного землеробства та забезпечення екологічної безпеки.
Оптимізація фітотоксичної дії гербіцидних сумішей у посівах озимої пшениці агроценозів степового екотипу
Keywords: grain; зерно; weeds; бур'яни; control; контроль; active substance; діюча речовина; pesticides; пестициди; resistance; стійкість; yield; врожайність